How many melanomas might be prevented if more people applied sunscreen regularly?. (22nd January 2018) - Olsen, C.M.; Wilson, L.F.; Green, A.C.; Biswas, N.; Loyalka, J.; Whiteman, D.C.
Summary: Malignant melanoma is the most dangerous of the commoner skin cancers, causing many thousands of deaths each year. It has become increasingly common in Western countries over recent decades. Exposure to ultraviolet rays from the sun is the major environmental factor causing melanoma. The application of sunscreen to the skin prior to sun exposure has been shown to reduce the risk of developing melanoma. This collaborative study between cancer epidemiologists in Brisbane, Australia and Manchester, U.K., explores the potential future impact of improved adherence to sunscreen use in Australia and the white population in the U.S.A. These populations were chosen because they have high rates of melanoma, and reliable comparative data on both melanoma incidence and current sunscreen use exist for these populations, allowing projections to be made. Using appropriate computer modelling tools, the study shows that if the populations adhered to a realistically achievable increase in sunscreen use (5% increase in use annually for 10 years from 2012), by 2031 there would be an 11% reduction in the incidence of malignant melanoma in the U.S.A. For Australia the reduction would be 10%. In contrast, if there was a maximum uptake of sunscreen use (100% of population using sunscreen with immediate effect) the corresponding reductions in melanoma by 2031 would be 38% and 34% respectively. These potential reductions in melanoma incidence in this study are rather disappointing, but do nevertheless represent a potential saving of thousands of lives each year with better adherence to sunscreen use. Abstract : Linked Article: Olsen et al. Br J Dermatol 2018; 178 :140–147